Estimating the economic burden of COVID-19 survivors in Punjab, Pakistan - Shumaila Abbas; Jamal Abdul Nasir; Rehan Ahmad Khan Sherwani (PLoS ONE, 2026)
Background The COVID-19 survivors are under a great deal of financial stress due to high medical costs, income lost during illness, and ongoing medical expenses. Many survivors borrow money, deplete their savings, or become more economically vulnerable. The situation becomes worse for the marginalized groups who do not receive enough support. Aims and objectives The pandemic has also had a significant financial and social impact on survivors in Pakistan. The present research aims to quantify the economic implications of COVID-19 on survivors from Punjab, Pakistan. Methods A cross-sectional study of 5045 survivors from Punjab, Pakistan, was conducted, and the economic burden of COVID-19 on survivors was quantified using a 27-item self-administered scale. Descriptive statistics, structural equation models, and odds ratios were computed to quantify the study’s objectives. Results The economic burden was classified into six constructs, representing the financial and social burdens of the disease on survivors. About 59.2% of the survivors were male, with an average age of 45.4 years, and 65.8% were employed in some capacity. The results depicted that the survivors aged over 45 years (OR=2.15, p < 0.01), admitted to hospital (OR=2.32, p < 0.01), infected severely (OR=2.11, p < 0.01), maximum secondary level of education (OR=2.18, p < 0.01), and disease duration up to 14 days (OR=5.05, p < 0.01) have an elevated financial burden than the opponent groups. The average duration of the disease was 12.1 days, and the daily cost of living and morbidity was estimated at 4763 PKR and 21286 PKR, respectively. Conclusion The financial burden of the disease not only affects survivors but also strains families and communities, underscoring the necessity of comprehensive support systems and policies to address the social and economic impacts of the pandemic on survivors. Policymakers should target healthcare cost containment, income support, and financial support to vulnerable groups such as women, unemployed individuals, and those infected with severe diseases.